Treating pneumonia in critical care in the United Kingdom following failure of initial antibiotic: A cost-utility analysis comparing meropenem with piperacillin/tazobactam - Edwards, S; Wordsworth, S; Clarke, M (2012)
Background: Treating patients admitted to critical care with severe pneumonia requires timely intervention with an effective antibiotic. This reduces the risk of dying of pneumonia and minimises complications associated with a prolonged stay in critical care. Objective: To compare the cost-effectiveness of meropenem 1 g/8 h with piperacillin/tazobactam 4.5 g/8 h for treating pneumonia in UK critical care. Methods: A Markov model was built to estimate lifetime costs and quality-adjusted life years (QALYs) of using meropenem versus piperacillin/tazobactam to treat severe pneumonia. Estimates of effectiveness, utility weights and costs were obtained from published sources. Probabilistic sensitivity analysis was conducted to address uncertainty in the model results. Results: Cost of treating a patient with severe pneumonia was estimated as £19,026 with meropenem and £19,978 with piperacillin/tazobactam, respectively. QALYs gained were 4.768 with meropenem and 4.654 with piperacillin/tazobactam. Probabilistic sensitivity analysis showed meropenem to be consistently less costly and more effective than piperacillin/tazobactam. Conclusion: The additional efficacy of meropenem translates into more patients surviving critical care and leaving this high-cost service more quickly than if they had been treated with piperacillin/ tazobactam. As meropenem is more effective and less expensive than piperacillin/tazobactam at treating patients with severe pneumonia, it is the dominant treatment option. © 2011 Springer-Verlag.